2016
DOI: 10.1166/jmihi.2016.1582
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Analysis of Human Voice for Assessment of Parkinson Disease

Abstract: Acoustic analysis of voice is a non invasive, reliable, easy to use and cost effective method in detecting parkinson disease. Voice deviation from normal one is the earliest indicator of parkinson disease. Voice data of sustained phonation is collected from 25 healthy and 22 parkinson subjects. The voice database is analyzed and acoustic features are extracted. Two new parameters ECP (energy between consecutive peaks) and ASR (average slew rate) are defined. The values of these parameters show variation among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Through extensive experiments, we demonstrated that a multimodal approach can improve neurological disease screening. Especially, adding voice features was effective for better generalization, which confirms existing reports on the importance of voice features 8 10 . From the single-protocol experiments, we observed that dynamic motions are more effective to screen stroke than simple ones.…”
Section: Conclusion and Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Through extensive experiments, we demonstrated that a multimodal approach can improve neurological disease screening. Especially, adding voice features was effective for better generalization, which confirms existing reports on the importance of voice features 8 10 . From the single-protocol experiments, we observed that dynamic motions are more effective to screen stroke than simple ones.…”
Section: Conclusion and Discussionsupporting
confidence: 86%
“…Another equally effective piece of data is voice. It is also well known that voices are good indicators of neurological diseases 8 10 and can be recorded using the same video cameras. Voice data are one-dimensional data where the data dimension is even smaller than a sequence of landmarks; therefore, it is also efficient in terms of computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…As for feature transformation, the frequently used algorithms are PCA (principle component analysis) [26, 27, 31, 49]. As for feature selection, the frequently used algorithms are NN (neural network) based [27–30, 32, 49], serial search based [2, 14, 29, 31], random based [32, 33, 48], p value based [2, 27–34], relevance based [35, 36] or entropy based [37], discrimination algorithm (DA) based [47]. As for classifier design, the predominantly used classifiers include a support vector machine (SVM) [1, 2, 14, 29, 32, 35, 38–41], KNN [1, 2, 26, 28, 40, 41, 47, 48, 49], random forest (RF) [2, 30, 36], Bayesian network [27, 28, 40, 42, 43, 48], discrimination algorithm (DA) [27, 29, 31, 37], probabilistic neural network (PNN) [27, 43] or decision tree [31, 40, 42, 44–46].…”
Section: Introductionmentioning
confidence: 99%